The role of INFL in code-switching: a study of a Papiamento heritage community in the Netherlands - Parafita Couto, M. Carmen; Pouw, Charlotte; Laanen, Rodi; López, Luis (Frontiers in Language Sciences, 2024)
In heritage bilingualism studies, code-switching has often been overlooked, with a focus on either the heritage language or the dominant societal language of the bilingual individual. However, exploring code-switching can provide valuable insights into heritage speakers' grammar, revealing patterns that may not be apparent when only examining monolingual speech. Recent research suggests that in code-switched clauses, functional elements must align with the language of verbal inflection (henceforth INFL), which encompasses Tense, Aspect, Voice, and Agreement. This generalization is usually referred to as the Matrix Language Frame (MLF). The present study explores the empirical validity of this generalization using an experimental protocol that controls for variables that earlier work did not take into consideration. These variables are: (i) adjacency between INFL and the functional element, (ii) the interaction of the MLF with Embedded Islands (henceforth EI), and (iii) the possibly degrading effects of inserting a functional category. Thus, the aim of this study is to provide evidence in support (or not) of the INFL constraint, beyond the experimental limitations in earlier work. The study focuses on the bilingual combination Papiamento-Dutch. Our results by-and-large support the MLF generalization.We carried out an online audio survey (3 point Likert scale) with 43 Papiamento-Dutch bilinguals. We manipulated the position of the switch and controlled for potential directionality effects by presenting code-switches in both switching directions.